674 TRANSITION FROM ESOPHAGECTOMY TO ENDOSCOPIC THERAPY FOR EARLY ESOPHAGEAL CANCER. (17th September 2021) - Reyhani, Arasteh; Dunn, Jason M; Santaolalla, Aida; Zylstra, Janine; Gimson, Eliza; Pennington, Mark; Baker, Cara R; Kelly, Mark; Van Hemelrijck, Mieke; Lagergren, Jesper; Zeki, Sebastian S; Gossage, James A; et al.
Abstract:  : To assess the outcomes of patients with early esophageal cancer (EEC) and high-grade dysplasia (HGD) comparing esophagectomy, the historical treatment of choice, to endoscopic eradication therapy (EET). Methods: Retrospective cohort study of consecutive patients with EEC/HGD, treated between 2000 and 2018 at a tertiary referral centre. Primary outcomes were all-cause and disease-specific mortality assessed by multivariable Cox regression and a propensity score matching sub analysis, providing hazard ratios (HR) with 95% confidence intervals (CIs), adjusted for age, tumor grade (G1/2 vs G3), tumor stage and lymphovascular invasion(LVI). Secondary outcomes included complications, hospital stay, and overall costs. Results: Among 269 patients, 133 underwent esophagectomy and 136 received endoscopic mucosal resection (EMR)+/−further EET. Adjusted survival analysis showed no difference between groups regarding all-cause mortality (HR 1.85, 95%CI 0.73, 4.72) and disease-specific mortality (HR 1.10, 95%CI 0.26, 4.65). In-hospital and 30-day mortality was 0% in both groups. The surgical group had a significantly higher rate of complications (Clavien-Dindo ≥3 26.3% vs EMR 0.74%), longer in-patient stay (median 14 vs 0 days EMR) and higher hospital costs ($20.426 vs $10.988 per patient). Conclusion: This series of patients with EEC/HGD treated during a transition period from surgery to EET, demonstrates a primary endoscopic approach does not compromise oncological outcomes with the benefit of fewer complications, shorter hospital stays, and lower costs compared to surgery. EET should be available as the gold standard treatment for patients with early esophageal cancer. Those with adverse prognostic features may still benefit from esophagectomy.